if g^2 -g-6 =0 and g< 0 what is the value of -3g
![if g2 g6 0 and glt 0 what is the value of 3g class=](https://us-static.z-dn.net/files/d55/0715f1513be155ca121aed37467dff8f.jpg)
Answer:
Step-by-step explanation:
g^2 - g - 6 = 0 can be factored as such:
g^2 + 2g - 3g - 6 = 0
g(g + 2) - 3(g + 2) = 0
(g - 3) (g + 2) = 0
g = 3, -2
Because g must be less than 0, 3, a positive number greater than 0, cannot be used to solve "-3g". So instead we use the other solution, -2:
-3(-2) = 6, the value of -3g.
Check:
(-2)^2 - (-2) - 6 = 0
(-2)^2 - (-2) = 6
4 - (-2) = 6
4 + 2 = 6